Tahqîq al-Manâth dalam Pembaruan Hukum Kewarisan Islam di Indonesia - Darmawan, Darmawan (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
Abstract: Tahqîq al-manâth is a process and effort to find law in Islamic lega tradition. It consists of three phases: (1) istinbât min al-nushûsh, extracting law from textual sources using literal interpretation, (2) idrâk al-wâqi', full comprehension of real legal cases by employing all necessary disciplines, and (3) tanzîl al-ahkâm ‘alâ al-wâqi', a step to apply law to cases using maqâshid as analytical instrument. Formulation of re-actualization of Islamic inheritance law in Indonesia is conducted by takhyir, which electively select appropriate legal opinion for implementation, talfiq, which is combining opinions of various schools of law, and takyif, which is adaptation and accommodation of external aspects that includes consideration to local custom in the formation of re-actualization of Islamic inheritance law in Indonesia. Key words: Tahqîq al-manâth, re-actualization, Islamic inheritance law